The U.S. Airways Group: A post-merger analysis - Manuela, Wilfred S, Jr (Archīum Ateneo, 2016)
America West Airlines acquired the bankrupt US Airways on September 27, 2005 to form the US Airways Group, improving its competitive position in the US airline industry. This paper analyzes the post-merger performance of the US Airways Group using airline operating metrics and financial ratios for the period 2005 to 2013. While the airline has still a long way to go to improve its leverage and liquidity ratios, its capital structure and ability to pay its obligations have improved since 2005. Moreover, although the airline is still inefficient in utilizing its assets, the efficiency improvements achieved since the merger have resulted in profits and positive returns to investors. Its share prices have also largely outperformed the S&P 500 and the XAL since the merger, an indication that investors are pleased with how the merger is developing over time. In view of the US Airways Group's improving financial and operating performance, the merger is, essentially, a success.